Obesity and dyslipidemia predict cardiac allograft vasculopathy and graft loss in children and adolescents post‐heart transplant: A PHTS multi‐institutional analysis. (5th February 2022) - Bogle, Carmel; Cantor, Ryan; Koehl, Devin; Lochridge, Jillien; Kirklin, James K.; Barnes, Aliessa; Wallis, Gonzalo; Amdani, Shahnawaz; Ameduri, Rebecca; Pahl, Elfriede; Simpson, Kathleen E.; Blume, Elizabeth D.
Abstract: Background: Obesity and dyslipidemia afflict children of all ages. We explored the prevalence of obesity and dyslipidemia in pediatric heart transplant (HT) recipients and its effects on cardiac allograft vasculopathy (CAV) and survival. Methods: This study included primary HT recipients (≤18 years) transplanted between 01/1996 and 12/2018 included in the Pediatric Heart Transplant Society database. Obesity was categorized according to WHO/CDC guidelines and dyslipidemia according to the National Cholesterol Education Program. Kaplan–Meier analyses for CAV and graft loss stratified for BMI and lipid panels were generated and risk factors identified using multivariate analyses. Results: Among 6291 HT patients (median age [range] at HT = 4.3 [0.6–12.8] years; 45% Female; 68% White), 56% had a normal BMI at HT. Obese patients at HT had an increased risk for graft loss (HR 1.19, 95% CI 1.01–1.4, p  = .04). Poor total cholesterol (TC), LDL‐C, and TG were associated with the risk of both CAV (HR 1.79, p  < .0001; HR 1.65, p  = .0015; HR 1.53, p  < .0001, respectively) and graft loss (HR 1.58, p  = .0008; HR 1.22, p  = .04; HR 1.43, p  = .0007, respectively). Conclusions: Pediatric patients who are obese at the time of HT and dyslipidemic at 1 year post‐HT are at an increased risk for CAV and graft loss. Preventative interventions may reduce morbidity and mortality among this cohort.